Go Nagai's Lion-girl [videorecording (DVD)] - Mitsutake, Kurando; Mitsutake, Kurando; Akari, Mami; Griffith, Tori; Raven, Damian Toofeek; Sakurai, David; Iwanaga, Joey; Mears, Derek (Cleopatra Entertainment ; Distributed by MVD Visual, 2023)
In the year 20XX, humanity has almost come to an end. A tsunami of meteors bombarded the entire planet. There were a very small number of survivors. They kill each other for more food, more power, causing 30 years of bloody civil war. The meteorites contain a mysterious ray inside the rock. If a human being is exposed to this ray, the cells in the body mutate and destroy themselves, causing certain death. But in very rare cases, some humans survive the exposure. Those who get exposed to the space ray and survive undergo a metamorphosis into horrific "meteorite beasts". People call them 'ANOROC'. ANOROC hunt and kill human beings for their lifeforce. ANOROC are the true enemy of humankind.Now, the Earth has the last defender of humanity against ANOROC; her name is 'LION-GIRL', a superhero Yakuza fighter and a true pursuer of Ninkyo.